EVALUATION THE HEPATOPROTECTIVE EFFECT OF QUERCETIN AGAINST ZINC OXIDE NANOPARTICLES INDUCED TOXICITY IN MOUSE MODEL - ANJUM, R; MAQSOOD, H; ANWAR, A; HUSSAIN, S; ALEEM, K; MOHSIN, S; ASLAM, S; KANWAL, S; AJMAL, A; AHMED, T; et al. (Biological and Clinical Sciences Research Journal, 2023)
Quercetin is a well-known flavonoid that resents in fruits and vegetables. Zinc oxide nanoparticles (ZnO-NPs) are widely used for packing and cosmetics. This study was conducted to determine the effect of Quercetin on the liver by ZnO-NPs toxicity in a mouse model. Thirty-six Swiss albino mice were divided into two groups, i.e. control group and the experimental group. The control group was administered saline for 28 days orally. The experimental group is further divided into three groups. To the first one, only ZnO-NPs (30 mg/kg, orally) were given for 28 days. To the second group, only quercetin (100 mg/kg, orally) was given for 28 consecutive days. To the third, a combination of quercetin and ZnO-NPs was given for alternate 28 days through the oral route. Animals were sacrificed after 14 and 28 days of dosing. Mouse liver was fixed in the 10% formalin to preserve organ integrity. Histopathological analysis was done to observe the structure of liver in treated mice. The ZnO-NPs group shows the central vein full of infiltrations, sinusoidal spaces congestions and some the necrosis of hepatocytes was observed. The quercetin group shows a normal central vein with no infiltrations. The animals that received both quercetin and ZnO-NPs showed infiltration in central vein and necrosis but less than that of only ZnO-NPs given group. Full recovery in the liver structure was observed in the quercetin+ZnO-NPs group after 28 days of treatment. This study showed the hepatoprotective effect of quercetin because it reduces the toxicity produced by ZnO-NPs.